The specification of glycinergic neurons and the role of glycinergic transmission in development - Chalphin, Alexander V.; Saha, Margaret S. (Frontiers in Molecular Neuroscience, 2010)
Glycine’s role as an inhibitory neurotransmitter in the adult vertebrate nervous system has been well characterized in a number of different model organisms. However, a full understanding of glycinergic transmission requires a knowledge of how glycinergic synapses emerge and the role of glycinergic signaling during development. Recent literature has provided a detailed picture of the developmental expression of many of the molecular components that comprise the glycinergic phenotype, namely the glycine transporters and the glycine receptor subunits; the transcriptional networks leading to the expression of this important neurotransmitter phenotype are also being elucidated. An equally important focus of research has revealed the critical role of glycinergic signaling in sculpting many different aspects of neural development. This review examines the current literature detailing the expression patterns of the components of the glycinergic phenotype in various vertebrate model organisms over the course of development and the molecular mechanisms governing the expression of the glycinergic phenotype. The review then surveys the recent work on the role of glycinergic signaling in the developing nervous system and concludes with an overview of areas for further research.